2019
DOI: 10.1155/2019/6490820
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Exposure to Cadmium Causes Persistent Changes in the Reproductive System in Female Wistar Rats

Abstract: Cadmium (Cd) is an environmental toxicant and endocrine disruptor in humans and animals, and recent studies have illustrated that the uterus is exceedingly sensitive to Cd toxicity. The aim of the study was to investigate the influence of subchronic (90 days) oral Cd exposure in daily doses of 0.09-4.5 mg/kg b.w. on the balance of sex hormones by estimating estradiol (E2) and progesterone (P) concentrations in the uterus and plasma in comparison with the effects of 17β-E2. Additionally, the uterine weight, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 69 publications
1
36
0
4
Order By: Relevance
“…In adult female Wistar rats exposed to cadmium, a statistically significant prolongation of the cycle was noted [ 40 ]. This effect was observed not only by the estrus phase but also by the diestrus phase.…”
Section: Cadmium (Cd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In adult female Wistar rats exposed to cadmium, a statistically significant prolongation of the cycle was noted [ 40 ]. This effect was observed not only by the estrus phase but also by the diestrus phase.…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…At the highest dose of cadmium (4.5 mg/kg bw), diestrus was extended, whereas proestrus was shortened although no significant increase in the duration of the cycle length was observed. Histopathological alterations in the ovaries of the cadmium-exposed rats were degeneration of the corpus luteum and damaged and fewer oocytes [ 40 ].…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…They also found that lower dose cadmium significantly increased the thickness of endometrium but in higher dose cadmium they found noticeable endometrial atrophy, therefore it concluded that cadmium can have both anti-estrogenic and estrogenic effect. 11 In this study, we found no significant difference in the control and experimental group, we theorize that this might be because we used lower dose and short amount of exposure time only. We also use whole smoke exposure thus there are many different chemical that might influenced the result of this study.…”
Section: Endometrial Thicknessmentioning
confidence: 51%
“…10 Based on previous study, it seems that the effect of cadmium exposures varies based on the dose and routes of administration. 11 Zhang, et al, conducts research on rat's endometrium given intraperitoneal cadmium and found thickening of the endometrium and myometrium, the study also stated that intraperitoneal cadmium causes inflammation in the endometrial stroma of the rats. 12 Da Costa et al, also conducted an experimental research on cadmium exposures by oral routes but they did not found any significant difference in the thickness of endometrium, however they found decrease of myometrium thickness in the experimental group.…”
Section: Endometrial Thicknessmentioning
confidence: 99%
“…Chronic Cd exposures has been reported to disturbed reproductive endocrine function, cause testes degeneration, decrease testicular mass [17][18][19], and decreased spermatozoa mobility [20] in male rats. Studies in female rats showed Cd accumulates in the female reproductive organs [9,14,[21][22][23][24]. In vivo studies have shown Cd administration to cause histopathological alterations in the ovary and uterus that include corpus luteum and granulosa cells degeneration, deceased oocytes population, increased luminal epithelial height and endometrial thickness [1,25,26] and disturbances in the concentrations of…”
Section: Introductionmentioning
confidence: 99%